Post-Christian Presupposition in Post-truth - Ezra Tari; Reinaldy Hank Rouw; Hengki Wijaya (Asosiasi Ahli Filsafat Keilahian Indonesia, 2020)
This paper attempts to describe the challenges and opportunities of social media in post-truth. The author will discuss this in this paper that is first the process of presuppositions formation. Second, post-Christian presuppositions. Third, build theological presuppositions. The author found that the need for institutions that spread can discover elements of hoax in the narrative. Second, agencies are watching the news and responding to public criticism. Third, there is a competition to create the actual content—fourth, literacy training. Fifth, there is a guarantee of freedom of expression.